The history of occupational health on the African continent - Michele A. Riva; Raz Dekel; Benoit Nemery; Paul D. Blanc; Rajen N. Naidoo (Journal of Occupational Medicine and Toxicology)
Abstract Background The history of occupational health on the African continent is important but under-studied. Methods We surveyed key resources related to medical history from the Ancient Egypt through the Ottoman Empire period. For the colonial era, we examined archival records, official reports, and historiographical studies, focusing on key cases from French North Africa, Belgian Congo, Italian East Africa, and British South Africa. To explore occupational health in Africa during the post-colonial period, we supplemented biomedical publications with data from governmental reports and policy documents. Results The history of occupational health on the African continent has been characterized by poor working conditions, especially in mineral extraction. Colonial exploitation frequently worsened these underlying problems. The post-colonial record suggests that many past deficiencies continue. Discussion An integrated approach to the history of occupational health on the African continent provides context for better understanding current problems and for anticipating future trends.